Confinement effects and acid strength in zeolites - Emanuele Grifoni (Nature Portfolio, 2021)
The structure of water around Brønsted acid sites in zeolites is shown to influence their catalytic activity. Here the authors shed light on confinement effects in different pores zeolites/water interfaces acidic strength by means of ab-initio molecular dynamics and enhanced sampling metadynamics techniques.